Bronquitis aguda, asociados a factores de riesgo en neonatos nacidos en El Hospital Martín Icaza de la ciudad de Babahoyo, Provincia Los Ríos. Periodo mayo-septiembre 2019 - Caicedo Tarira, Katherine Roxana (2019)
The research work developed has its origins in the Martín Icaza Hospital in Canton Babahoyo, capital of the Province of Los Ríos, the research focuses on infants born in them who have acute bronchitis from or after birth. This research maintains the general objective; Identify the risk factors and complications of acute bronchitis in neonates born at Martin Icaza Hospital in Canton Babahoyo, during the period May-September 2019. This is intended to radically reduce the incidence of this disease in newborns. The methodology used in this research has been the deductive and inductive method, maintaining a qualitative and quantitative research modality, in addition to the type of research; Field, bibliographic and descriptive. The study population of this research is based on the number of infants born at Martin Icaza Hospital during the May - September period. According to the survey applied to parents with newborns who have symptoms or the pathology itself, it was found that most do not know the symptomatology of this disease in newborns and at the same time they do not have the slightest idea of what they are the risk factors that affect the outbreak of acute bronchitis in neonates. In turn, respondents state that they would like to stay informed about this pathology, its causes, symptoms and treatment to avoid possible future relapses in their children.